Accreditation of undergraduate programs at the Autonomous University of Zacatecas, Mexico - Morales Alvarado, Alba Lucia; Pérez Veyna, Óscar; Salcedo Triana, Oralia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim of this study is to analyze the accreditation processes of undergraduate programs at the Autonomous University of Zacatecas (UAZ), to identify opportunities for the consolidation of the process and programs. The approach is qualitative, the methodology used was institutional document review and semi-structured interviews with former officials, which were transcribed, coded and analyzed with the ATLAS.ti software. It is concluded that the consolidation of accreditation processes in the UAZ is a utopia. However, opportunities were identified as input for the ongoing University Reform Process.